PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL: KOMITMEN TUJUAN SEBAGAI VARIABEL INTERVENING (STUDI EMPIRIS PADA RUMAH SAKIT TIPE A, B, DAN C, DI JAWA TENGAH DAN DAERAH ISTIMEWA YOGYAKARTA) - Sugiyanto, Eko; Subagiyo, Lilik (Universitas Muhammadiyah Surakarta, 2005)
The influence of budgetary participation to managerial performance has been examined inseveral accounting studies with conflicting result. The conflicting evidence may reflect the influence ofother variables. This study examined the influence of budgetary participation to managerialperformance through goal commitment as intervening variable. The population of this study is managers at hospital type A, B, and C in central java andDIY. The sample of this research is collected with contact person and mail survey method. Fromabout of 400 questionnaires delivered, only 72 questionnaires returned and ready to analyze. Thetechnique for examining hypothesis is path analysis. The result of this study showed that budgetary participation has positive effect to managerialperformance. Other result that is shown in this study is that budgetary participation has positiveeffect to goal commitment, goal commitment has positive effect to managerial performance, andbudgetary participation has positive effect to managerial performance through goal commitment asintervening variable.